International agile teams in digital and virtual environment - Liška, Radek (2017)
The thesis discusses research on a selected international team that incorporates agile methodology framework. The team is distributed among multiple European states and has off-shore members in India. The research questions include cross-cultural aspects of teamwork, organizational viewpoint as well as other key areas of team cooperation. Analysis is performed based on questionnaire distribution and a series of structured interviews with members of the researched team. Research findings include a list of recommended changes to team organization and evaluation of cross-cultural and factors of cooperation and their impact. Research has provided an action plan and a set of research observations that include deep analysis of teamwork, the area has proven to be attractive for further research, hence the thesis is concluded with suggestions in this area.